Micro Hydro SZ 200 Pump Power Plant System as Turbine where The Blade Runner Tip is Made Almost 2 mm of Radius and Induction Motor as Generator - P. MELIALA (NIM 13104109), EFRATA
The scarcity of energy that happen nowadays stimulating demand for alternative energy with the budget constraint and friendly to environment. The natural source of water with small debit in the remote area actually can be exploited. The function of using mixed flow pump can be converted to be turbine by turning back the rotation where the induction-motor is used as generator, very effective in PLTMH so the investment price is cheaper. It is cheaper, since the supply of the pumps and the induction motor is abundant in the market. In the application ideally the load that is received by consumers has constant voltage and frequency. This trial controls the adjustment of constant voltage manually by changing of the valve. The voltages in this trial are 200v, 220v, and 240v with varying maximum load. At the experiment, the available flow rates were restricted around 0.0668 m3/s, so the maximum efficiency retrieved was 71.27 % with the rotation of 1100rpm and the load was 1,8kW. But the efficiency can be increased until it reaches optimal condition of 82,27% at the rotation of 1100 rpm, flow rate of 0.0945 m3/s and load 9kW. According to the experiments which were done, it is expected that PLMTH like this can be realized as one of the power plant in Indonesia as the solution of the energy scarcity issues.